The participation role of the researcher as a co-operative achievement - Goico, Sara (Social Interaction. Video-Based Studies of Human Sociality, 2021)
In this paper, I examine my role as a researcher doing video-based fieldwork in mainstream classrooms with deaf youths in Iquitos, Peru through the lens of participation frameworks that emerged within moments of situated interaction. While conducting video-based fieldwork, I attempted to primarily occupy the role of a passive participant-observer in order to capture the deaf students’ everyday interactions with minimal interference from the researcher. As I will develop in the paper, it is evident that my status within the classroom participation frameworks was dynamic. While I often was not attended to in the participation framework and positioned as a ratified overhearer of the unfolding interaction, my status could quickly shift as the students and teacher responded to my presence. Moments when my status in the participation framework changed make visible the various roles that I occupied in the classroom, from an observer, to a confidant, to an authority figure. Through interactional extracts, I illustrate how the roles that I occupy in the classroom social ecology are a moment-by-moment co-operative achievement between members of the class and myself.